Flowering and Fruiting Phenology of Caesalpinia coriaria (Jacq.) Wild - Deepakkumar, R.; Ramanan, S. Suresh (Indian Journal of Hill Farming, 2016)
Caesalpinia coriaria (Jacq.) Wild is an evergreen species which have rich amount of tannins in pods, fodder and ornamental value. To understanding the floral phenology will helps us to expeditiously utilize the tree in urban landscapes, avenues and agroforestry systems. Production of superior quality seedling starts from the selection of superior trees, collection of good quality pods for which there is a need to understand the floral phenology and the harvesting index. The present investigation revealed that C. coriaria was starts flowering from Mid-September to October. It was observed that a mean of 41 flowers per inflorescence with pod set and having a seed set percentage around 2-4 %. The pods attains harvest maturity at 21st week after anthesis indicating a distinctive colour change from yellowish brown to darker brown colour. Seeds are orthodox in nature and has a 70% germination rate. Floral phenology will help us to understand, reproductive biology of C. coriaria and will help to know much more about the species.